Exploring Media-Based Interventions for Adolescent Mental Health: Literature Review - Choirunissa, Risza; Nugraheni, Sri Achadi; Purnami, Cahya Tri; Wahyuningsih, Nur Endah (Poltekkes Kemenkes Palu, 2023)
Media-based interventions show promise in addressing the rising mental health concerns among adolescents, surpassing challenges associated with traditional care. This review critically assesses the effectiveness of media-based interventions in promoting adolescent mental health, with a specific focus on social media, digital applications, and film. The methodology employs a comprehensive approach, utilizing Google Scholar, Scopus, and PubMed databases (2012-2022) with keywords such as